DOMINANT FACTORS AFFECTING SEAWEED (Gracilaria verrucosa) PRODUCTION IN ACID SULFATE SOILS-AFFECTED PONDS OF LUWU REGENCY, INDONESIA - Akhmad Mustafa; Jesmond Sammut (Indonesian Aquaculture Journal, 2010)
Most of brackish water ponds used for seaweed (Gracilaria verrucosa) culture in Luwu Regency, South Sulawesi, Indonesia are constructed on acid sulfate soil. Despite this inevitable condition, opportunities remain open to increase the seaweed production. The research was conducted to study the dominant factors that affect the seaweed production in ASS-affected ponds of Luwu Regency. As a dependent variable in this research is seaweed production. Independent variables were grouped into: (a) farmer status factor, consisting of 9 variables; (b) pond condition factor, consisting of 8 variables; (c) pond management factor, consisting of 29 variables; (d) soil quality factor, consisting of 17 variables and (e) water quality factor, consisting of 11 variables. Multiple regression with dummy variable was used to analyze the data in prediction dependent variable. Results show that the average of seaweed production in ASS-affected pond of Luwu Regency is 11,000 kg dry/ha/year. Seaweed production can be increased through: (a) decreasing dosage of urea and KCl and increasing dosage and frequency of fertilizer containing phosphate; (b) increasing water depth in the pond and decreasing percentage of water exchange,(c) conducting remediation to increase the soil pH and decreasing the concentration of Fe in the water, (d) increasing stocking density of milkfish to decrease the epiphyte population and (e) increasing the frequency of the farmer to attend trainings.